Developing the Next Generation of Leaders in Health Policy and Management: Lessons From an Undergraduate Student-Led Organization - Thomas, Charlotte; Sandhu, Sahil; Li, Josee; Sanders, Gillian D.; Prvu Bettger, Janet (Frontiers in Public Health, 2022)
As health care continues to evolve, training the next generation of healthcare leaders is more important than ever. However, many university undergraduate students are not directly exposed to topics such as health policy and management within their coursework or co-curricular engagements. At Duke University, we developed the Student Collaborative on Health Policy (SCOHP) as an inter-disciplinary health policy hub that offers opportunities for learning, engagement, and leadership in the healthcare-related fields for students of all academic backgrounds. We see opportunity for similar student-led groups to be established by student leaders at other institutions, increasing interaction with experts, mentorship and the accessibility of experiential education, service, and leadership in the health care sector.